A Lewis‐Acid‐Catalyzed Phenolic Ether 'O to C' Rearrangement: Synthesis of 4‐Aryldihydrocoumarins. Issue 7 (20th May 2019) - Kumar, Praveen; Kunkalkar, Rupesh A.; Fernandes, Rodney A.
Abstract: An efficient O to C rearrangement of phenolic ethers is developed. The Lewis acid BF3 ⋅OEt2 (0.5 equiv) could catalyze the O to C migration of β‐aryloxy‐β‐arylesters to β, β‐bis‐arylesters, thereby the free phenolic OH cyclizes with the ester group, resulting in the formation of 4‐aryldihydrocoumarins. Abstract : On Call: An efficient O to C rearrangement of β‐aryloxy‐β‐arylesters to β, β‐bis‐arylesters is described. The free phenolic OH group cyclizes with the ester, resulting in the formation of 4‐aryldihydrocoumarins.